Comparative Performance Analysis of Green Bond Issuers to their Conventional Counterparts - Farag, Mai Hosam (AUC Knowledge Fountain, 2024)
This thesis conducts a comparative performance analysis of green bond issuers versus their conventional counterparts. In the context of the 2015 Paris Climate Agreement, which underscores the financial sector's role in promoting environmental sustainability, green bonds have emerged as crucial instruments for financing eco-friendly projects. This research investigates the financial performance of firms issuing green bonds using metrics such as sales growth, return on assets (ROA), and total debts through Ordinary Least Squares (OLS) regression analysis. The analysis covers 54 publicly traded bonds issued in North America between 2018 and 2022. Despite the growing popularity of green bonds, there are conflicting views regarding their financial benefits. While some studies suggest that green bonds lead to superior financial performance due to heightened investor demand and enhanced brand recognition, others argue that the high costs and stringent regulations associated with green bonds may negate these benefits. This thesis aims to contribute to this ongoing debate by providing a comprehensive comparative analysis of green bond issuers and traditional bond issuers. The findings of this study are significant for investors, shareholders, and policymakers interested in sustainable finance and its potential to foster long-term economic growth and environmental stewardship. By examining the financial impacts of green bond issuance, this research seeks to provide deeper insights into the viability and benefits of green bonds as a tool for promoting sustainable development.